ANALISIS PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN DAN STANDAR OPERASIONAL PROSEDUR TERHADAP KINERJA PEGAWAI PADA DINAS PEMBERDAYAAN MASYARAKAT DESA KABUPATEN MAJENE - abdul waris; Muhammad Idris; Muhammad Hidayat (AkMen JURNAL ILMIAH, 2020)
The research aims to know and analyze influence mangement information systems and operational standard procedures in partial and simultan as well as the most dominant variables to performance employees in the empowerment departement of poeople for the village in Majene regency. The population in this research were all of the employee in the empowerment departement of poeople for the village in Majene regency which consisted of 43 people and sample was selected by aturated sampling, so that all of the population takes as sample which consisted of 43 people employees in the empowerment departement of poeople for the village in Majene regency. This research used survey method with regression analysis technique, and the questionnaries as instrument with likert scaled. The result of research indicate that mangement information systems and operational standard procedures in partial and simultan influence positive and significant. And the most dominant variables to influence performance employees is mangement information systems with beta standardized (0,362) >( 0,311).